Necroptosis Signaling Promotes Inflammation, Airway Remodeling, and Emphysema in Chronic Obstructive Pulmonary Disease - Lu, Zhe; Van Eeckhoutte, Hannelore P.; Liu, Gang; Nair, Prema M.; Jones, Bernadette; Gillis, Caitlin M.; Nalkurthi, B. Christina; Verhamme, Fien; Buyle-Huybrecht, Tamariche; Vandenabeele, Peter; Vanden Berghe, Tom; Brusselle, Guy G.; et al. (American journal of respiratory and critical care medicine, 2021)
Rationale: Necroptosis, mediated by RIPK3 (receptor-interacting protein kinase 3) and MLKL (mixed lineage kinase domain-like), is a form of regulated necrosis that can drive tissue inflammation and destruction; however, its contribution to chronic obstructive pulmonary disease (COPD) pathogenesis is poorly understood. Objectives: To determine the role of necroptosis in COPD. Methods: Total and active (phosphorylated) RIPK3 and MLKL were measured in the lung tissue of patients with COPD and control subjects without COPD. Necroptosis-related mRNA and proteins as well as cell death were examined in lungs and pulmonary macrophages of mice with cigarette smoke (CS)-induced experimental COPD. The responses of Ripk3-/- and Mlkl-/- mice to acute and chronic CS exposure were compared with those of wild-type mice. The combined inhibition of apoptosis (with the pan-caspase inhibitor quinoline-Val-Asp-difluorophenoxymethylketone [qVD-OPh]) and necroptosis (with deletion of Mlkl in mice) was assessed. Measurements and Main Results: The total MLKL protein in the epithelium and macrophages and the pRIPK3 and pMLKL in lung tissue were increased in patients with severe COPD compared with never-smokers or smoker control subjects without COPD. Necroptosis-related mRNA and protein levels were increased in the lungs and macrophages in CS-exposed mice and experimental COPD. Ripk3 or Mlkl deletion prevented airway inflammation upon acute CS exposure. Ripk3 deficiency reduced airway inflammation and remodeling as well as the development of emphysematous pathology after chronic CS exposure. Mlkl deletion and qVD-OPh treatment reduced chronic CS-induced airway inflammation, but only Mlkl deletion prevented airway remodeling and emphysema. Ripk3 or Mlkl deletion and qVD-OPh treatment reduced CS-induced lung-cell death. Conclusions: Necroptosis is induced by CS exposure and is increased in the lungs of patients with COPD and in experimental COPD. Inhibiting necroptosis attenuates CS-induced airway inflammation, airway remodeling, and emphysema. Targeted inhibition of necroptosis is a potential therapeutic strategy in COPD.